PENGARUH KUALITAS WEBSITE DAN KEPERCAYAAN TERHADAP KEPUTUSAN PEMBELIAN ONLINE PADA APLIKASI MOBILE SHOPEE - Nur Chotimah (Jurnal Ilmiah Manajemen "E M O R", 2019)
The purpose of this study was to determine the user's perception of the quality of the website owned by the Mobile Application Shopee and the effect from variable quality of website and trust in online purchasing decisions. The study was conducted on 138 respondents who are students at IKIP Muhammadiyah Maumere. Dimensions WebQual: usebaility, information quality and interaction quality is used to measure the quality of a website. The Results of the research indicate that the quality of the website is good, than website quality and trust factor proved to be positive and significant influence the online purchasing desicion.